KAJI EKSPERIMENTAL RETROFIT R404A DENGAN REFRIGERAN RAMAH LINGKUNGAN R290 PADA FREEZER - Kasni Sumeru; Triaji Pangripto Pramudantoro; Apip Badarudin; Ridwan Nugraha; Luga Martin Simbolon; Mohamad Firdaus bin Sukri (Jurnal Teknologi Terapan, 2023)
R404A refrigerant is still widely used as the working fluid in freezers with temperatures below -30°C. However, because of R404A’s high global warming potential (GWP) value, its use as a working fluid should be stopped immediately. One alternative is an environmentally friendly refrigerant, that is R290. In this study, the R404A refrigerant was replaced by R290 in a freezer that can reach -40°C. In the case of replacing a refrigerant with a different type, the reference used is the same charging volume in the system. The filling mass of R290 is the ratio of the density of R404A to R290 at its evaporation temperature, which is -40°C. The amount of R404A’s mass filling is 170 g, while the amount of R290’s mass filling is 62.9 g. Based on a 120-minutes testing, replacing R404A with R290 has resulted in the reduction of power input by 6.0%, as well as in the slight increase of its cooling capacity, which is 2.42%. As a result of the input power decrease and the cooling capacity increase, the COP in the freezer also increased, namely by 8.05%. More importantly, if a leak occurs in the refrigerant, the replacement of R404A with R290 can help reduce gas emissions that contribute to global warming. It is because the GWP value of R404A refrigerant, which is 3922, is replaced by the GWP value of R290 refrigerant, which is only 3.